ICT Integration in Educational curriculum in Higher Education: Challenges and opportunities in the University of Rwanda-College of Education - Mushimiyimana, Jean Baptiste; Bazimaziki, Gabriel; Tuyishime, Dieudonné (International Journal of Humanities and Education Development (IJHED), 2024)
Information and Communication Technology is significantly relevant in all domains of today’s economy specifically in higher education. In this study, the researchers wanted to identify the opportunities and challenges available in the ICT integration with particular interest in educational curriculum at the University of Rwanda - College of Education. Framed on Constructive theory, the study is not only descriptive but also quantitative as it includes some quantifiable information. Using Yamane’s table of sample determination; 150 respondents were selected from 1984 people. Questionnaire, observation and focused discussions were used as research instruments. Results disclosed a range of ICT opportunities such as computer laboratories, loudspeakers and microphones, internet, projectors and personal mobile phones among others. As to how those resources are used profitably; findings revealed the provision of online assignments; urging students to use social networks responsibly especially for academic purposes, using personal computers, projectors, audio equipment and internet sharing in their daily practices of teacher - education journey. The identified challenges affecting effective integration of ICT in education include insufficiency of computers, limited skills of using ICT resources; slow network; big class size and for lecturers’ overload, among others. Findings also revealed that there is a need for provision of enough computers to students; increase of connectivity and other ICT infrastructure; reduction of lecturers’ workload and number of students in one classroom; train people in ICT usage and design a dual - mode policy to allow students and lecturers to use it as an accepted way of learning paired with the normal face to face method.